Ontology metadata for ontology reuse. (1st January 2011) - Simperl, Elena; Sarasua, Cristina; Ungrangsi, Rachanee; Bürger, Tobias
Ontologies are often poorly documented, thus being hardly accessible to users and ontology reuse services. A first step towards a better ontology documentation is an explicit schema for their systematic description. To offer an informed background for such a schema we surveyed ontology engineering technology, and the types of ontology-related descriptive means they use. The result is part of the OMV standard, and was evaluated through professional reviews. A second step is the provision of automatic techniques to acquire such documentation, for which we devised the Ontology MEtadata GenerAtion (OMEGA) algorithm, presented in the second part of the paper.